Expressions of NF-κB and downstream inflammatory factors in the kidney of insulin resistance rat - Shuang-tong, YAN; Chun-lin, LI; Ju-ming, LU; TIAN, Hui; Zhao-yan, GU; LIU, Yu (Jie fang jun yi xue za zhi, 2014)
Objective　To investigate the variation and significance of the expressions of NF-κB, inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in the renal tissue of insulin-resistant rat. Methods　Thirty healthy male Wistar rats were bred since 2 months old, and they were randomly divided into normal control (NC) group (n=15) and insulin-resistant (IR) group (n=15). Insulin resistance rat model was reproduced by feeding with high fat and sucrose diet. Hyperinsulinemic-euglycemic clamp test was used to verify the reproduction of the model. The kidneys of the rats were obtained after the successful reproduction of the model. The change in renal histology was observed by HE staining, and the expressions of iNOS and COX-2 in the kidneys were detected by immunohistochemistry staining. The mRNA expressions of NF-κB, iNOS and COX-2 in the kidneys were assessed with RT-PCR. DNA binding activity of NF-κB in the rat's kidney was assessed with electrophoretic mobility shift assay (EMSA). Results　HE staining sh